2016
DOI: 10.1016/j.jpeds.2016.06.063
|View full text |Cite
|
Sign up to set email alerts
|

School-Age Test Proficiency and Special Education After Congenital Heart Disease Surgery in Infancy

Abstract: Objective To evaluate test proficiency and the receipt of special education services in school-age children who had surgery for congenital heart disease (CHD) <1 year of age. Study design Data from Arkansas-born children who had CHD surgery at Arkansas Children's Hospital at <1 year of age from 1996–2004 were linked to state birth certificates and the Arkansas Department of Education longitudinal database containing achievement test scores in literacy and mathematics for grades 3-4 and special education code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 39 publications
(57 reference statements)
0
35
0
Order By: Relevance
“…Our previous qualitative study on barriers and limitations at work showed that less physical work was beneficial for our patients. 10,[29][30][31][32] Since this study demonstrates a positive effect on employment and limitations at work from higher education, efforts should be undertaken to maximize academic attainment in this population. However, patients with CHD are at increased risk for neurodevelopmental disorders.…”
Section: Predictors For Employment and Limitations At Workmentioning
confidence: 89%
“…Our previous qualitative study on barriers and limitations at work showed that less physical work was beneficial for our patients. 10,[29][30][31][32] Since this study demonstrates a positive effect on employment and limitations at work from higher education, efforts should be undertaken to maximize academic attainment in this population. However, patients with CHD are at increased risk for neurodevelopmental disorders.…”
Section: Predictors For Employment and Limitations At Workmentioning
confidence: 89%
“…Children with CHD, compared to those without, are also more likely to receive special education services, have lower academic achievement scores, and report more school absenteeism . However, less is known about how functional limitations are associated with educational outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have documented that children with congenital heart disease (CHD) have a higher prevalence of cognitive and motor limitations compared to their peers . Additionally, children with CHD are more likely to receive special education services and are at higher risk for grade retention . The etiology of these limitations is most likely multifactorial and may be due to genetic or chromosomal abnormalities, abnormalities in fetal brain development secondary to altered cerebral circulation in utero, as well as perioperative factors including single ventricle physiology, hospital length of stay, and duration of cardiopulmonary bypass …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been estimated that up to one‐half of all children with congenital heart disease (CHD) may have subsequent, usually subtle, neurodevelopmental impairment. While the neurodevelopmental and academic achievement outcomes for these children at both preschool and school ages are not related to the underlying cardiac anatomy or type of surgery, children with a history of CHD are 50% more likely to require special education services than those without CHD . Studies performed in the general population report that only 10% of children between 9 and 24 months of age with developmental delay receive early intervention and therapeutic services, and less than 30% receive interventions prior to school entry .…”
Section: Introductionmentioning
confidence: 99%